2007
DOI: 10.1097/01.aog.0000284625.10175.31
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Regulatory T Cells Specific for Paternal Antigens During Pregnancy

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 41 publications
4
72
2
1
Order By: Relevance
“…These data are in agreement with those from other research groups (10, 17). Moreover, IL-10 levels were significantly diminished and TGF-␤ levels were slightly diminished in pathological pregnancies compared with normal pregnancies, further suggesting low Treg numbers in pathological pregnancies, since Treg are known to affect immune responses by secreting antiinflammatory cytokines at the fetal-maternal interface (14,61,67). Thus, our data on low levels of hCG coinciding with low levels of Treg-associated molecules suggest that hCG may be chiefly responsible for Treg attraction to the fetal-maternal interface.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These data are in agreement with those from other research groups (10, 17). Moreover, IL-10 levels were significantly diminished and TGF-␤ levels were slightly diminished in pathological pregnancies compared with normal pregnancies, further suggesting low Treg numbers in pathological pregnancies, since Treg are known to affect immune responses by secreting antiinflammatory cytokines at the fetal-maternal interface (14,61,67). Thus, our data on low levels of hCG coinciding with low levels of Treg-associated molecules suggest that hCG may be chiefly responsible for Treg attraction to the fetal-maternal interface.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, it has been demonstrated that Treg from women with recurrent spontaneous abortion were functionally deficient, as higher numbers were required to exert a similar magnitude of suppression as compared with Treg from fertile women (60). In mice, Treg are generated immediately after fertilization and expand at the periphery, being specific for paternal Ags (61). Accordingly, paternal lymphocyte immunization used in the clinical practice to improve pregnancy outcome in women with previous recurrent abortions (62) is able to augment the number of male-specific suppressor T cells (63).…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] As it was discussed already, seminal fluid is pivotal in expanding Treg 39 and local application of TGF-b in the mice had the same effect. 40 The antigen specificity of Treg was demonstrated both in a mouse model by Schumacher and Zhao in 2007 23,41 and in human by Tilburgs. 42 As for the mechanisms of action of Treg during pregnancy, it has been proposed that they act by creating a local tolerant microenvironment 43 that IL-10 and PD-1 but not TGF-b or CTLA-4 are relevant for pregnancy.…”
Section: Tafurimentioning
confidence: 99%
“…16 This could, however, not explain why Treg are necessary before implantation 17,22 and the fact that Treg from non-pregnant mice or from pregnant females carrying third party fetuses cannot confer fetal protection in a model of disturbed tolerance. 17,23 It was Sarah Robertson's pioneer work that introduced the concept of seminal fluid as the first antigen source that activates the maternal immune system and prepares for pregnancy establishment. 24 In their review, Robertson and collaborators summarize current evidences as how the seminal fluid elicits a female immune response and particularly concentrate on the events leading to generation and expansion of Treg in the peri-conception and peri-implantation period.…”
Section: Tafurimentioning
confidence: 99%
See 1 more Smart Citation